Human Capital Strategy in Enhancing Business Performance: The Moderating Role of External Environment - Aziz; Rahmadanti Puspita (Jurnal Pustaka Cendekia Pendidikan, 2024)
This study aims to examine the influence of Human Capital on Business Performance and the moderating role of the External Environment in private banks in Jambi. The research method used is a quantitative approach with a survey as the main instrument. The research respondents were private bank employees selected based on the criteria of having worked for at least one year and being directly involved in operational activities related to achieving business performance. The collected data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS), which allows for simultaneous testing of relationships between latent variables. The results show that human capital plays a significant role in improving bank business performance. Good human resource quality, reflected in employee competence, skills, motivation, and professionalism, contributes to increased operational efficiency, customer service quality, and bank competitiveness. This study also found that the external environment acts as a moderating variable that strengthens the relationship between human capital and business performance. When external conditions are supportive, such as economic stability, conducive banking regulations, and market competition that encourages innovation, the contribution of human capital to business performance becomes greater. This study emphasizes the importance of human resource management strategies that are integrated with the dynamics of the external environment. Practically, these findings provide direction for private bank management to not only focus on developing employee quality, but also be adaptive to changes in the business environment in order to achieve sustainable performance.